# Integration

Mahesh Tutorials Science 49
GROUP (A)-HOME WORK PROBLEMS
Q-1) ( )

7
7 –
x
x dx
Ans. ( )

7
7 –
x
x dx
=
∫ ∫
7
7 –
x
dx x dx
= +
∫ ∫
8
7

log7 8
x
x
c
Q-2) ( )
4 2 x
x 3x 2x 5cosx 7e + − − +

Ans. Let I = ( )
4 2 x
x 3x 2x 5cosx 7e + − − +

( )
5 3 2
x
x 3x 2x
5 sinx 7e
5 3 2
c = + − − + +

5
3 2 x
x
x x 5sinx 7e
5
c = + − − + +
Q-3)
7 4
2
4 3
x 5x dx
x
x
| |
− + −
|
\ ¹

Ans. Let, I =
7 4
2
4 3
x 5x dx
x
x
| |
− + −
|
\ ¹

=
8 5
x 5x 1
4 3 2 x c
8 5 x
| |
− + − − × +
|
\ ¹
=
8
5
x 4
x 6 x c
8 x
− − − +
Q-4)
( ) ( )
2
2
4 5 4x 2sin 3 2x
dx
x
5cosec 3
5
(
+ − −
(
(
| |
+ −
( |
\ ¹ ¸ ¸

Ans. Let,I =
( ) ( )
2
2
4 5 4x 2sin 3 2x
dx
x
5cosec 3
5
(
+ − −
(
(
| |
+ −
( |
\ ¹ ¸ ¸

( ) ( ) ( )
3
2 cos 3 2x 4 5 4x
1
3 4 2
x
5 cot 3
5
c
1
5
− − +
= × − +

| | | |
− −
| |
\ ¹ \ ¹
+

( )
( )
3
5 4x x
cos 3 2x 25cot 3 c
3 5
+
| |
= − − + − +
|
\ ¹
Q-5) f′ (x) = 4x
3
– 2x + 1
Ans. We know,
f (x) = ( ) f ' x dx

=
( )
3
4x 2x 1 dx − +

=
4 2
4x 2x
x c
4 2
− + +
∴ ∴∴ ∴ f (x) = x
4
– x
2
+ x + c ... (i)
∴ ∴∴ ∴ f (x) = 2
4
– 2
2
+ 2 + c
∴ ∴∴ ∴ 17 = 16 – 84 + 2 + c ( ) f 2 17 = (
¸ ¸

∴ ∴∴ ∴ f (x) = x
4
– x
2
+ x + 3 [ from i]
Q-6)
| |
+
|
\ ¹

2
1
x dx
x
Ans.
= + +

2
2
1
2 x dx
x
= + +
∫ ∫ ∫
2
2
1
2 1 x dx dx dx
x
= + +
3
1
2 –
3
x
x c
x
Q-7)

1
1–
dx
x
Ans. = + – log 1– x c
Q-8)
( )

3
1
1–
dx
x x
Ans.
( )
+

3 3
3
1–
1–
x x
x x

Integration
50 Mahesh Tutorials Science
( ) ( )
= +

3 3
3 3
1–
1– 1–
x x
x x x x
( )
( )
( )
( )
+ +
= +
∫ ∫
2
3
1– 1
1
1–
1–
x x x
dx dx
x
x x
( )
( )
= + + +
∫ ∫
–3 2
1
1
1–
x x x dx dx
x
( )
= + + +

–3 –2 –1
1
1–
x x x dx dx
x
( )
= + + +
–2
log 1– –1
log
–2 –1
x x
x c
x
( )
= + + +
–2
log 1– –1
log
–2 –1
x x
x c
x
( )
= + + +
2
1– –1 1
– log log
–1
2
x
x c
x
x
= + +
2
–1 1
– log
1–
2
x
c
x x
x
Q-9)
2
7 –19 –15
1– 3
x x
x
Ans. I =
+

2
15 19 – 7
3 –1
x x
dx
x
Required integral,
I =
| |
+ +
|
\ ¹

1
5 8
3 –1
x dx
x
= + + +
2
log 3 –1 5
8
2 3
x x
x c
Q-10) If
( ) = − +
3
' 4 2 1 f x x x and f (2) = 17, find f(x)
Ans. ( )
′ =

f x dx
( )
= +

3
4 – 2 1 x x dx
= + +
4 2
4 2

4 2
x x
x c
( ) = + +
4 2
– f x x x x c
( ) ( ) ( ) = + +
4 2
2 – 2 2 f x c
= + + 16 – 4 2 c
( ) = (
¸ ¸
∵ 2 17 f
( ) = + +
4 2
– 3 f x x x x
Q-11)
6x 8
dx
2x 1

Ans. Let, I =
6x 8
dx
2x 1

Here,
3
6x 8
2x 1 6x 8
2x 1
6x 3
5
+ −

⇒ − −

∴ ∴∴ ∴
6x 8 5
3
2x 1 2x 1

= −
− −
So, I =
6x 8
dx
2x 1

=
5
3 dx
2x 1
| |

|

\ ¹

=
5 2
3 1.dx dx
2 2x 1

∫ ∫
=
5
3x log 2x 1 c
2
− − +
Q-12)
2
3x 4x 2
x 1
+ −

Ans. Here,
2
3x 4x 2
x 1
+ −

2
2
3x 7
x 1 3x 4x 2
3x 3x
7x 2
7x 7
5
+ −
− +
+
⇒ − + −

+
Let, I =
2
3x 4x 2
dx
x 1
+ −

=
5
3x 7 dx
x 1
| |
+ +
|

\ ¹

=
2
3x
7x 5log x 1 c
2
+ + − +
Integration
Mahesh Tutorials Science 51
Q-13)
2
8x 10x 2
2x 1
+ −
+
Ans. Here,
2
8x 10x 2
2x 1
+ −
+
2
2
4x 3
2x 1 8x 10x 2
8x 4x
6x 2
6x 3
5
− −
− −
+
⇒ + + −
+

+

Let, I =
2
8x 10x 2
dx
2x 1
+ −
+

=
5
4x 3 dx
2x 1
| |
+ −
|
+
\ ¹

=
5 2
4 x dx 3 1 .dx dx
2 2x 1
+ −
+
∫ ∫ ∫
=
2
4x 5
3x log 2x 1 c
2 2
+ − + +
Q-14)
2
3x 6x 2
2x 3
+ −

Ans. Here,
2
3x 6x 2
2x 3
+ −

2
2
3x 21
2 4
2x 3 3x 6x 2
9x
3x
2
21x
2
2
21x 63
2 4
55
4
+ −
− +
+
⇒ − + −

Let, I =
2
3x 6x 2
dx
2x 3
+ −

=
55
3x 21
4
dx
2 4 2x 3
| |
|
+ +
|

|
|
\ ¹

=
3 21 55 2
x dx 1.dx dx
2 4 8 2x 3
+ +

∫ ∫ ∫
=
2
3x 21x 55
log 2x 3 c
4 4 8
+ + − +
Q-15)
3 2
3x 7x 7x 1
3x 4
+ + +
+
Ans. Here,
3 2
3x 7x 7x 1
3x 4
+ + +
+
2
3 2
3 2
2
2
5
x 3x
3
3x 4 3x 7x 7x 1
3x 4x
3x 7x 1
3x 12x
5x 1
20
5x
3
23
3
− −
− −
+ +
+ −
⇒ + + + +
+
+ +
+
− +
− −
Let, I =
3 2
3x 7x 7x 1
dx
3x 4
+ + +
+

2
23
5
3
x 3x dx
3 3x 4
| |
|
= + − +
|
+
|
|
\ ¹

3 2
x 3x 5 23 3
x dx
3 2 3 6 3x 4
= + − +
+

3 2
x 3x 5 23
x log 3x 4 c
3 2 3 6
= + − + + +
GROUP (B)-HOME WORK PROBLEMS
Q-1) I =
2
(cos 3x + 4 sin x – 2 sin x)

dx
Ans. = cos 3x dx + 4

sin x dx – 2

x
1 – cos 2x
2

dx.
cos 3x dx 4 sinxdx 1.dx cos 2x dx = + − +
∫ ∫ ∫ ∫
=
sin 3x
3
– 4 cos x – x +
sin 2x
2
+ c
Integration
52 Mahesh Tutorials Science
Q-2) sin 8x cos 4x

dx
Ans. =
1
2
2 sin 8x cos 4x

dx
=
1
2
sin 12x + sin 4x

dx
= –
cos 12x
24

cos 4x
8
+ c
Q-3) sin 3x sin 2x ×

dx
Ans. =
1
2
2 sin 3x sin 2x

dx
=
1
2
cos x – cos 5x

=
sin x
2

sin 5x
10
+ c
Q-4) cos 7x cos 5x

dx
Ans. =
1
2
2 cos 7x cos 5x

dx
=
1
2
cos 12x + cos 2x

dx
=
sin 12x
24
+
sin 2x
4
+ c
Q-5)

2
sin xdx
Ans.
=

1– cos2
2
x
dx
=
∫ ∫
1 cos2
2 2
x
dx dx
=

1 1
– cos2
2 2
x xdx
= +
1 1 sin2

2 2 2
x
x c
| |
= +
|
\ ¹
1 sin2

2 2
x
x c
Q-6)
2
(tan x – cot x)

dx
Ans. =
( )
2 2
tan x + cot x – 2

dx
=
( )
2 2
sec x – 1 + cosec x – 1 – 2

dx
=
2
sec x dx

+
2
cosec x dx

– 4 dx

= tan x – cot x – 4x + c
Q-7)
2
(tan 2x + cot 2x)

dx
Ans. = ( )
2 2
tan 2x + cot 2x + 2

dx
=
2 2
sec 2x – 1 + cosec 2x – 1 + 2

=
tan 2x
2

cot 2x
2
+ c
Q-8)
sin x + cosec x
tanx

dx
Ans. =
1
sin x +
sin x
sinx
cos x

dx
=
2
2
(sin x + 1)
sin x

cos x dx
=
cosec x
1 +
sin x
| |
|
\ ¹

cos x dx
= cos dx

+ cosec x cot x

dx
= sin x – cosec x + c
Q-9)
x x
x
e cos x 4 tanx
dx
4 cos x
| |

|
|
\ ¹

Ans. =
x
e
dx
4
| |
|
\ ¹

– sec x tan x dx

=
x
e
4
e
log
4
| |
|
\ ¹
| |
|
\ ¹
– sec x + c
=
x
x
e
4 (1 – log4)
– sec x + c
Q-10)
x x
x
e sin x + 3 cot x
dx
3 sin x

Ans. =
x
e
dx
3
| |
|
\ ¹

+ cot x cosec x

dx
=
x
x
e
3 (1 – log 3)
– cosec x + c
Integration
Mahesh Tutorials Science 53
Q-11)
tanx
sec x – tan x

dx
Ans. =
sin x
1 – sin x

dx
=
2
(1 + sin x) sin x
1 – sin x

dx
=
2
2
sin x + sin x
1 – sin x

dx
=
( )
2
2
sinx + sin x
cos x

dx
=
( )
2
sec x tanx tan x +

dx
= tan x sec x dx

+
2
sec x dx

– 1 dx

= sec x + tan x – x + c
Q-12)

sin .sin mx nx dx
Ans.
=

–1
–2sin .sin
2
mx nx dx
( ) ( ) | + |
=
|
+
\ ¹

cos cos – 1

2 –
m n x m n x
dx
m n m n
( ) ( ) | + |
=
|
+
\ ¹
∫ ∫
cos cos – 1

2 –
m n x m n x
dx dx
m n m n
( ) ( )
( )
+ (
=
(
¸ ¸
–sin sin –
1

2 – –
m n x m n x dx
m n m n
( ) ( ) + (
= +
(
+
¸ ¸
sin – sin
1

2 –
m n x m n x
c
m n m n
Q-13)
{ }
–1 –1
cos (sin x) + tan (cot x)

dx
=
–1
cos cos – x
2
π ( | |
| (
\ ¹ ¸ ¸

+tan
–1 tan – x
2
π ( | |
| (
\ ¹ ¸ ¸
dx
=
x x
2 2
π π | |
− + −
|
\ ¹

dx
= ( ) 2x π −

dx
= dx π

– 2x dx

= x – x
2
+ c
Q-14)
+

tan
tan sec
x
x x
Ans.
+

sin
cos
sin 1
cos cos
x
x
dx
x
x x
=
+

sin
1 sin
x
dx
x
( )
=
∫ 2
1– sin
sin
1– sin
x
x
x
( )
+
=

2
2
sin sin
cos
x x
dx
x
( )
= +

2
tan .sec tan x x x dx
= +
∫ ∫ ∫
2
tan .sec sec 1 x xdx xdx dx
= sec x + tan x – x + c
GROUP (C)-HOME WORK PROBLEMS
Q-1)
+

1– tan
1 tan
x
dx
x
Ans. =
+

sin
1–
cos
sin
1
cos
x
x
dx
x
x
=
+

cos – sin
cos sin
x x
dx
x
Substitute cosx + sin x = t
Differentiate w.r.t. x
( ) + = cos sin
d dt
x x
dx dx
( ) = + = –sin cos
dt
x x
dx
( ) ∴ = cos – sin x x dx dt
= = +

log
dt
I t c
t
I = log (sin x + cos x) + c
Q-2)
( ) +

1
2 3log
dx
x x
Ans.
=
+

1
2 3log
x
dx
x
Integration
54 Mahesh Tutorials Science
=
+

3
1
3 2 3log
x
dx
x
( ) +
=
+

2 3log
1
3 2 3log
d
x
dx
dx
x
= + +
1
log 2 3log
3
x c
( )
( )
( )
′ ¦ ¹
¦ ¦
= +
´ `
¦ ¦
¹ )
∵ log
f x
dx f x c
f x
Q-3)
sin x
2 + cos x

dx
Ans. Let f(x) = 2 + cos x
f′ (x) = – sin x
= –1
–sin x
2 + cos x

dx
= –1
f (x)
f(x)

∫ dx
= – log |f (x)| + c
= – log |2 + cos x| + c
Q-4)
cos x
5 + sin x

Ans. Let f (x) = 5 + sin x
f′ (x) = cos x
∴ ∴∴ ∴
cos x
5 + sin x

dx
= log |5 + sin x| + c
Q-5)
+

1
sec tan
dx
x x
Ans. =
+

1
1 sin
cos cos
dx
x
x x
=
+

cos
1 sin
x
dx
x
Put sin x = t
cos x dx = dt
=
+

1
dt
t
= + + log 1 t c
= + + log 1 sinx c
Q-6)
1
x + x log x

dx
Ans. =
1
x (1 + log x)

Let f (x) = 1+ log x
f′ (x) =
1
x
∴ ∴∴ ∴ I =
1
x (1 + log x)

dx
= log |1 + log x| + c
Q-7)
x
x
e
2 + 5 e

dx
Ans. Let f (x) = 2 + 5e
x
f′ (x) = 5e
x
∴ ∴∴ ∴
1
5
x
x
5 e
2 + 5 e

dx
=
1
5
log |2 + 5e
x
| + c
Q-8)
x –x
x –x
e + e
e – e

dx
Ans. Let f (x) = e
x
– e
–x
f′ (x) = e
x
+ e
–x
∴ ∴∴ ∴ I=
x –x
x –x
e + e
e – e

dx
= log |e
x
– e
–x
| + c
Q-9)
2
1 + tan x
3 + 4 tan x

dx
Ans. =
2
sec x
3 + 4 tan x

dx
Let f (x) = 3 + 4 tan x
f′ (x) = 4 sec
2
x
∴ ∴∴ ∴ I =
1
4
2
4 sec x
3 + 4 tan x

=
1
4
log |3 + 4 tanx| + c
Integration
56 Mahesh Tutorials Science
So,
I =
( ) ( )
2x 2x
2x
7
1 4e 5 8e
8
4e 5
(
− − +
(
(

(
¸ ¸

dx
= – 1

. dx +
2x
2x
7 8e
dx
8
4e 5 −

= – x +
2x
7
log 4e 5 c
8
− +
Q-7)
1
dx
1 tanx +

Ans. I =
1
1 tanx +

dx

1
dx
sinx
1
cos x
=
+

cos x
dx
cos x sinx
=
+

1 2cos x
dx
2 cos x sinx
=
+

( ) ( ) ( )
( )
cos x sinx cos x sinx
1
dx
2 cos x sinx
+ + −
=
+

( )
( )
cos x sinx 1
1. dx dx
2 sinx cos x
( −
= +
(
+
(
¸ ¸
∫ ∫

1
x log sinx cos x c
2
= + + ( +
¸ ¸
Q-8)
1
dx
1 cot x +

Ans. I =
1
dx
1 cot x +

1
dx
cos x
1
sinx
=
+

sinx
dx
sinx cos x
=
+

1 2sinx
dx
2 sinx cos x
=
+

( ) ( ) ( )
( )
sinx cos x sinx cos x
1
dx
2 sinx cos x
+ + −
=
+

( )
( )
cos x sinx 1
1.dx dx
2 sinx cos x
( −
= −
(
+
(
¸ ¸
∫ ∫

1
x log sinx cos x c
2
= − + ( +
¸ ¸
Q-9)
x
x
2e 3
dx
2e 3
+

Ans. I =
x
x
2e 3
dx
2e 3
+

( )
( )
( )
x
x
2e 3 6
dx
2e 3
− +
=

x
6
1.dx dx
2e 3
= +

∫ ∫

x
x
6e
x
2 3e

= +

dx

x
x
3e
x 2
2 3e

= +

dx

x
x 2log 2 3e c = + − +
Q-10)
+

4 – 5
4 5
x
x
e
dx
e
Ans.
( )
( )
=

4 – 5 – 4 – 5
4 – 5
x x
x
e e
e
( )
=
∫ ∫
2 log 4 – 5 – 1
x
e dx
= +

2 log 4 – 5 –
x
e x c
GROUP (E)-HOME WORK PROBLEMS
Q-1)
+

sinx 4
dx
sin2x
Ans. Let I =
+

sinx 4
dx
sin2x

= +
∫ ∫
sinx
4 cos ec2x
2sinx.cos x

| |
= +
|
\ ¹
∫ ∫
1
sec x 4 cosec2x
2
Integration
Mahesh Tutorials Science 57

+
| |
= + +
|
\ ¹
4log tanx c
1
log sec x tanx
2 2
I =
+ + +
1
log sec x tanx 2log tanx c
2
Q-2)
+

2sinx 5cos x
sin2x

= +
∫ ∫
3sinx 5cos x
I
sin2x sin2x

= +
∫ ∫
sinx cos x
3 5
2sinx.cos x 2sinx.cos x

= + +
∫ ∫
3 5
sinx cos ecx c
2 2
I =
+ + +
3 5 x
log sec x tanx log tan c
2 2 2
Q-4)
cos 4x
dx
sin2x

Ans. I =
+

2
2sin 2x 1
sin2x
=

+
∫ ∫
2
2sin 2x 1
sin2x sin2x
= +
∫ ∫
–2 sin2x cos ec2x
=
( )
+

–2 – cos 2x
1
log cosec2x cot 2x
2 2
=
1
log tanx cos 2x c
2
+ +
=
+ +
1
log cos ec2x – cot 2x cos 2x c
2
Q-5)
sinx
dx
sin2x

Ans. I =
sinx
dx
sin2x

=
sinx
2sinx cos x

dx
=
1
sin x dx
2

=
1
log sec x tanx c
2
+ +
Q-6)
cos (x + a)
dx
cos x

Ans. =
cos x cos a – sin x sin a
dx
cos x

= cos a 1 dx – sin a

tan x dx

= x cos a – sin a · log |sec x| + c
Q-7)
sin (x + a)
dx
cos x

Ans. =
sin x cos a + cos x sin a
dx
sin x

= cos a 1 dx + sin a cot x dx
∫ ∫
= x cosa + sina · log |sinx| + c
Q-8)
cos (x + a)
dx
sin x

Ans. =
cos x cos a – sin x sin a
dx
sin x

= cos a cot x dx – sin a

1 dx

= cos a log |sin x| – x sin a + c
Q-9)
sin (x + a) dx
dx
sin (x – a)

Ans. =
sin (x – a + 2a)
dx
sin (x – a)

=
sin (x – a) cos 2a + sin 2a cos (x – a)
dx
sin (x – a)

= cos 2a 1 dx + sin 2a

cot (x – a)

dx
= x cos 2a + sin2a log |sin(x – a)|+ c
Q-10)
cos (x + a)
dx
cos (x – b)

Ans. =
( ) ( ) ( )
( )
cos x b a b
dx
cos x b
− + +

=
cos (x – b) cos (a + b) – sin (x – b) sin (a + b)
dx
cos (x – b)

= cos (a + b) 1 dx – sin (a + b)

tan (x – b) dx

= x cos(a + b) – sin(a + b) log |sec (x – b)| + c
Integration
58 Mahesh Tutorials Science
Q-11)
cos (x + 2a)
dx
cos (x – 2a)

Ans. =
( ) cos x 2a 4a
dx
cos (x – 2a)
− +

=
cos (x – 2a) cos 4a – sin(x – 2a) sin 4a
dx
cos (x – 2a)

= cos 4a 1 dx – sin 4a

tan (x – 2a) dx

= x cos 4a – sin4a log |sec(x – 2a)| + c
Q-12)
sin (x + 2a)
dx
sin (x + a)

Ans. =
sin (x + a + a)
dx
sin (x + a)

=
sin (x + a) cos a + cos (x + a) sin a
dx
sin (x + a)

= cos a 1 dx + sin a

cot (x + a) dx

= x cosa + sina log |sin (x + a)| + c
Q-13)
cos x
dx
cos (x +2a)

Ans. =
cos (x + 2a – 2a)
dx
cos (x + 2a)

=
cos (x + 2a) cos 2a + sin (x + 2a) sin 2a
dx
cos (x + 2a)

= cos 2a 1 dx + sin 2a

tan (x + 2a) dx

= x cos 2a + sin 2a log |sec (x + 2a)| + c
Q-14)
1
dx
sinx cos x +

Ans. Let, I =
1
dx
sinx cos x +

1 1
1 1
2
sin cos
2 2
dx
x x
=
+

1
2
cos sin sin cos
4 4
dx
x x
π π
=
+

1
2
sin
4
dx
x
π
=
| |
+
|
\ ¹

2 cos
4
ec x dx
π | |
= +
|
\ ¹

2 log tan
2 8
x
c
π | |
= + +
|
\ ¹
Q-15)
1
dx
sinx 3 cos x +

Ans. Let, I =
1
dx
sinx 3 cos x +

1 1
2 1 3
sin cos
2 2
dx
x x
=
+

1 1
2
cos sin sin cos
3 3
dx
x x
π π
=
+

1 1
2
sin
3
dx
x
π
=
| |
+
|
\ ¹

1
cos
2 3
ec x dx
π | |
= +
|
\ ¹

1
log tan
2 2 6
x
c
π | |
= + +
|
\ ¹
Q-16)
( ) ( )
1
dx
cos x a sin x b − −

Ans. Let, I =
( ) ( )
1
dx
cos x a sin x b − −

( )
( )
( ) ( )
cos b a
1
dx
cos b a cos x a sin x b

=
− − −

( )
( ) ( )
( ) ( )
cos x a x b
1
dx
cos b a cos x a sin x b
− − − (
¸ ¸
=
− − −

( )
( ) ( ) ( ) ( ) ( )
( ) ( )
1
cos b a
cos x a cos x b sin x a sin x b
dx
cos x a sin x b
=

− − + − −
− −

( )
( ) ( )
1
cot x b dx tan x a dx
cos b a
(
= − + −
¸ ¸

∫ ∫

( )
( ) ( )
1
log sin x b log sec x a c
cos b a
( = − + − +
¸ ¸

( )
( ) ( )
1
log sin x b log cos x a c
cos b a
( = − − − +
¸ ¸

Integration
Mahesh Tutorials Science 59

( )
( )
( )
sin x b 1
log c
cos b a cos x a

= +
− −
Q-17)
( )
( ) +

cos – x a
dx
cox x a
Ans.
( )
( )
+
+

cos – 2
cos
x a a
x a
( ) ( )
( )
+ +
=
+
cos cos2 – sin sin2
cos
x a a x a a
x a
( ) = +

cos2 1– tan sin2 a x a a
( ) = +
∫ ∫
cos2 1– sin2 tan a a x a
= + cos2 – sin2 log sec – x a a x a c
( ) = + + cos2 – sin2 log cos x a a x a c
Q-18)
( ) ( )

1
sin – sin –
dx
x a x b
consider cot A – cot B
=
cos cos

sin sin
B
A B
=
sin cos – cos sin
sin .sin
B A B A
A B
( )
=
sin –
sin .sin
B A
A B
( )
=
cos – cot 1
sin – sin .sin
A B
B A A B
Now, we replace A by x – a and B by x – b
B – A = (x – b) – (x – a) = a – b
( ) ( )
( )
( ) ( )

=
cot – – cot –
sin –
1
sin – sin –
x a x b
a b
x a x b
This is possible a – b ≠ ≠≠ ≠ nπ ππ π,
Where n is integer.
Because if a – b = nπ ππ π then, sin (a – b) = 0 and
division by sin (a – b) is impossible
( ) ( )

1
sin – sin –
dx
x a x b
( ) ( )
( )
=

cot – – cot –
sin –
x a x b
dx
a b
( )
( ) ( ) = (
¸ ¸ ∫
1
cot – – cot –
sin –
x a x b dx
a b
( )
( )
( )
¦ ¹
¦ ¦
= +
´ `
¦ ¦
¹ )
log sin –
1
sin –
– log sin –
x a
c
a b
x b
Now, if a – b = nπ ππ π,
Where n is integer, then – b = nπ ππ π – a
∴ ∴∴ ∴ sin (x – b) = sin (x + nπ ππ π – a)
= sin (nπ ππ π + x – a)
= ± sin (x – a) + sin if n = even, – sig if
n = odd.
Then,
( )
=
±
∫ 2
sin –
dx
I
x a
( )
= ±
∫ 2
sin –
dx
x a
( ) = ±

2
cos – ec x a dx
( ) = ± + cot – x a c
GROUP (F)-HOME WORK PROBLEMS
Q-1)
2
1
dx
9x + 6x + 5

Ans. =
1
9

2
1
dx
2 5
x x +
3 9
+

=
2
1 1dx
2x 1 5 1
9
x
3 9 9 9
+ + + −

=
1
9

2 2
1
dx
1 2
x + +
3 3
| | | |
| |
\ ¹ \ ¹

=
1
9

1
2
3
· tan
–1

1
x +
3
2
3
| |
|
|
\ ¹
+ c
=
1
6
tan
–1

3x + 1
2
| |
|
\ ¹
+ c
Q-2)
2
1
dx
x + x + 1

Ans. =
2
1
1 1
x x 1
4 4
+ + + −

2
2
1
dx
1 3
x + +
2 2
=
| |
| |
|
|
|
\ ¹
\ ¹

Integration
60 Mahesh Tutorials Science
1
3
2
=
·
1
1
x
2
tan
3
2

| |
+
|
|
|
|
\ ¹
+ c

1
2 2x 1
tan
3 3

+ | |
=
|
\ ¹
+ c
Q-3)
2
5
dx
4 – 2x – x

Ans. = – 5
2
1
dx
x + 2x – 4

= – 5
2
1
dx
x + 2x + 1 – 5

= –5
( )
2
2
1
dx
(x + 1) – 5

= + 5
( )
2
2
1
dx
5 – (x + 1)

=
1
5
2 5
×
log
5 + x + 1
5 – x – 1
+ c

5 5 x 1
log c
2 5 x 1
+ +
= +
− −
Q-4)
2
1
dx
x – 6x – 7

Ans. =
2
1
dx
x – 6x + 9 – 16

=
2 2
1
dx
(x – 3) – 4

=
( )
1
2 4
log
( )
( )
x 3 4
x 3 4
− −
− +
+ c
=
1
8
log
x – 7
x + 1
+ c